Reflexivity in Facebook interaction – Enregisterment across written and spoken language practices. (June 2015) - Stæhr, Andreas
Abstract: The focus of this article is how linguistic reflexivity, the organization of linguistic features and the normative behavior following from these processes takes place across online and offline activities among a group of adolescents who daily interact with one another though several modes of communication. In the paper I argue that written discourse have taken up a much more important role in people׳s everyday discursive practices because of the widespread availability and impact of social media. As a consequence of this I make the claim that spoken and written discourse in combination should be considered when studying everyday language use and processes of enregisterment. In this article I illustrate how young people from a linguistically and culturally diverse area of Copenhagen use linguistic features indexical of speech styles in their linguistic practices on Facebook. I study how the use of such linguistic resources points towards different stereotypes and what sense of rights and sanctions are involved in the reactions to the use of these different types of marked language use. I study this to discuss how spoken language practices and practices associated with writing co-contribute to similar processes of enregisterment.